Analisis Spasial Zona Potensi Penangkapan Ikan (ZPPI) Menggunakan Parameter SST dan Klorofil-a di Wilayah Pesisir Bali Utara - Putri Indraswari; Wahyudi Ali Mahrus; Nanda Kristian Putra; Andi Ro’uf Syaifulloh; Ilham Aditya Saputra; I Made Satya Graha; Jhon Jhohan Putra Kumara Dewa (Prodi PWK Universitas Tadulako, 2026)
This study aims to analyze the potential of Fishing Ground Zones (ZPPI) in the coastal waters of North Bali using Sea Surface Temperature (SST) and chlorophyll-a concentration parameter. A descriptive quantitative and spatial approach was applied, utilizing Level 3 Aqua MODIS satellite imagery collected from January 2021 to January 2025. The analysis identified three zonation categories: potential zones (271.65 km²), less potential zones dominating most of the study area, and non-potential zones (50.1 km²). Although SST and chlorophyll-a are theoretically positively correlated with fishery productivity, linear regression tests revealed a very weak relationship, with the highest R-squared value of only 0.092 in 2024, suggesting that other oceanographic factors — such as Indonesian Throughflow dynamics and terrestrial nutrient runoff — play a more dominant role in driving chlorophyll-a variability in this region. Spatial distribution of potential zones is concentrated in strategic coastal areas near small island clusters and entirely within the 12-nautical-mile boundary, making them accessible for small-scale fishers. This study contributes a remote-sensing-based spatial dataset of ZPPI that can serve as a reference for sustainable coastal resource management planning in North Bali.